(untitled) (Journal of Universal Science Research, 2025)
This article explores the anatomical and topographical structure of the legs in cattle, their role in movement, and the physiological principles necessary for understanding foot diseases. The legs of cattle, as the locomotor and support apparatus, consist of bones, muscles, tendons, ligaments, and joints. The interrelationship between these structures ensures the movement of the animals. During movement, coordination between the legs, the amortization mechanisms, and the functional distribution of muscles maintain the stability of the body. This article serves as a scientific foundation for a deeper understanding of the locomotor system in cattle and for taking effective measures against its disorders in the field of veterinary medicine.